(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The incidence of the disease varies from 30 to 35% among the entire pathology of the oral mucosa (OOM), affecting mainly women of the climacteric period and menopause [Kubanova A. A. 2010, Perlamutrov Yu.N. 2010, Julia S. Lehman 2009]. Psychoemotional stress is considered to be one of the triggering factors in the onset of LPO OCPR, and the activity of the processes of free radical oxidation of lipids and the lack of capacity of the antioxidant potential of the body determine the ineffectiveness of therapy, as a result of which it can be concluded that it is necessary to include drugs with antioxidant and anxiolytic properties in the traditional treatment regimen. In this study, 60 patients with erosive ulcerous form were examined and treated according to the treatment method. They were randomly assigned to the same treatment group: Group I – Celestodera applications were used in complex treatment: Solcoseryl, in group II - combined treatment (Tisol applications with L-arginine in combination with injections of platelet autoplasma). In both cases positive dynamics was noted, however, the nature and timing of epithelialization was different.